(3ZGjI GdeQGO hQGMI GdaDGOs - (3GdHbGYj, GdTGaYj, CMeOs
(3ChdgG (B:s
(3HYO GdHSedI ; GdMeO ddg GdPj LYd GdYGTbjf HEMcGe GdZQGe QVi hMHH Edjge GdehJ aj MH ef jghhfg adG Jcf jG aJi HGdYOd eYJQVG s
(3BNQgG (B:s
(3hbO LeYJ gPG GdeLehY ef cJH cKjQI eG jRjO Ydi eGFI cJGH eYJeOI aefgG eQhL GdPgH ddeSYhOj hYLGFH GdHdOGf hYLGFH GdeNdhbGJ hcJGH bUU GdCfHjGA ddcSGFj hcJGH bUU GdCfHjGA ddKYGdHj hef GdeLGejY GdRQGa (B( (3cPG (B) (3ccJGH GdeSJWQa hZjQg ef GdeLGejY hLYdJg LGeYG dcd af ef Gdafhfs
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdbWQjIs
(3ehGUaGJ GdhYGA (B:s
(3Qbej edhfs
Keywords: (3GdeYGQa GdYGeIs